2019
DOI: 10.1002/oby.22403
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐Induced Obesity in Cannabinoid‐2 Receptor Knockout Mice and Cannabinoid Receptor 1/2 Double‐Knockout Mice

Abstract: Objective Evidence suggests that cannabinoid‐1 receptor (CB1R) activation is associated with increased food intake and body weight gain. Human epidemiological studies, however, show decreased prevalence of obesity in cannabis users. Given the overlapping and complementary functions of the cannabinoid receptors (CB1R and CB2R), mice lacking CB2R and mice lacking both CB1R and CB2R were studied. Methods A high‐fat diet was used to study metabolic changes in male mice lacking CB2R (CB2−/−) or lacking both CB1R an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
3
13
1
Order By: Relevance
“…Another study reported in two-month-old male CB 2 −/− mice similar body weight values to those of normoglycaemic, age-matched, wild-type mice [18]. Increased body weight of CB 2 −/− mice was measured in other studies [19,35], which is in accordance with our data considering male CB 2 −/− mice only.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another study reported in two-month-old male CB 2 −/− mice similar body weight values to those of normoglycaemic, age-matched, wild-type mice [18]. Increased body weight of CB 2 −/− mice was measured in other studies [19,35], which is in accordance with our data considering male CB 2 −/− mice only.…”
Section: Discussionsupporting
confidence: 92%
“…In feeding mouse models, CB 2 receptor deletion was associated with impaired glucose clearance [19], supporting our findings of elevated blood glucose and hormonal differences in CB 2 −/− . Using diet-induced obesity mice, CB 2 receptor agonists were shown to be efficacious in reducing body weight and obesity-associated metabolic parameter, e.g., insulin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been demonstrated that the EC system modulation is involved in regulating obesity [90,91], but CB1 and CB2 receptors play different roles. While CB1 activation induces increasing inflammatory processes [92], CB2 activation ameliorates the inflammatory state related to obesity [93]. Actually, there are different opinions about the role of CB2 in obesity.…”
Section: The Ec System In Obesity and Fatty Liver Diseasementioning
confidence: 99%
“…Indeed, children expressing this variant show an increase in weight and high levels of pro-inflammatory cytokines (IL-6 and TNF-α). When the CB2 receptor is selectively stimulated with JWH-133, this critical condition is restored in primary cultures of adipocytes obtained from obese subjects [93,98,99]. Another polymorphism positively associated with obesity is the FAAH polymorphism rs324420 that reduces FAAH activity, leading to higher AEA levels and consequent over-activation of CB1 receptors, which, in turn, causes adipogenesis and a high obesity risk [100,101].…”
Section: The Ec System In Obesity and Fatty Liver Diseasementioning
confidence: 99%